Medication Adherence and Physical Activity in Relation to Blood Pressure in Hypertension Patients - Mahendra Mardaningrat, Gede Ari; Wiguna, Putu Dony Astika; Lestari, I Dewa Ayu Made Dian; Gayatri, Dewa Ayu Agung Maya; Mardaningrat, Kadek Herdana Vildan; Krisnanda, Made Yogi (PT Inovasi Pratama Internasional, 2023)
In the 21st century, it is estimated that there will be a rapid increase in the incidence and prevalence of NCDs. It is estimated that the countries that will feel the impact the most are developing countries, including Indonesia. One of the NCDs that is currently a very serious health problem is hypertension. This study aims to determine the relationship between medication adherence and physical activity on blood pressure in hypertension patients. This research is an analytical study with a cross-sectional design. Data collection was carried out by conducting interviews with patients, filling out questionnaires by the patient, viewing the patient's medical record data and carrying out blood pressure checks in September 2023 to October 2023. Bivariate analysis showed that there was an influence of medication attendance (p value = 0.0001; PR = 7.667) and physical activity (p value = 0.0001; PR = 26.156) on blood pressure. Multivariate analysis showed that physical activity (p value = 0.0001; aPR = 23.726) had more influence on blood pressure than medication adherence (p value = 0.007; aPR = 6.622). It is important for health workers to always educate patients regarding medication compliance and increase physical activity in an effort to achieve normal blood pressure.